Predicting the long-term social and ecological impacts of tree-planting programs: Evidence from northern India. (April 2021) - Rana, Pushpendra; Miller, Daniel C.
Highlights: We demonstrate a novel approach to understanding long-term impacts of public forest plantations. Predictive proxy indicators (PPIs) can help predict and track long-term impacts of public forest plantations. We use process-tracing and qualitative comparative analysis to validate PPIs for community-oriented plantations. Secure property rights, community-led monitoring and enforcement, and seedling survival rate are key PPIs. Abstract: Planting trees has long been a major forest improvement and management activity globally. Forest plantations take years, even decades to mature and establish. Yet most national and international projects to support plantations are of relatively short duration, which presents a major challenge to near-term accountability as well as assessment of longer-term social and ecological impacts. Here, we address this challenge by identifying and empirically validating a set of predictive proxy indicators (PPIs)—measures on key variables taken during program implementation that are predictive of longer-term impacts—for community-oriented tree-planting efforts in northern India. Using process-tracing and qualitative comparative analysis, we find that clusters of PPIs explained vegetation growth trajectories and other outcomes over more than a decade in 23 randomly selected public forest plantations in Kangra district, Himachal Pradesh. PPIs relating to property rights and local livelihood benefits, community-led monitoring and enforcement, and seedling survival rate, together, were associated with successful long-term forest plantation outcomes, including more tree cover and socio-economic benefits for local communities. The causal pathways identified in this study suggest that measuring and comparing indicator values in specific spatial and temporal contexts can help to assess the likelihood and directionality of the long-term social and ecological impacts of forest plantations. In addition to the empirical contribution it makes, this study also demonstrates a novel approach to understanding long-term impacts of public forest plantations relevant to country contexts around the world.